Short-term outcome of endovascular stenting for symptomatic vertebrobasilar stenosis - Mohamed Abdel moneim Abdo Tolba; Mohammed Alaswad; Mohamed Mohamed Tawfik; Ahmed Zaki Akl; Mona Ali Eissa; Hala El-khawas; Hani Mahmoud Zaki Eldin; Mohamed Khaled Ahmed Elewa (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Stroke is a global health concern, causing blood supply interruption to the brain. Vertebrobasilar stenosis (VBS) is the main concern, causing stroke or ischemic attacks. Treatment includes antithrombotic therapy and lifestyle modifications, but invasive intervention like endovascular angioplasty is needed in indicated patients. This study aims to investigate the short-term outcome of endovascular stenting, especially, drug-eluting stents (DES) for symptomatic vertebrobasilar stenosis. In this prospective cohort study, we selected patients with ischemic events, including transient ischemic attack (TIA) or non-disabling stroke, diagnosed by CT or MRI brain, MRA, and over 70% diameter stenosis of the basilar or vertebral artery suggested by angiography. Patients with previous stent at the target lesion, acute stroke, heavily calcified lesion, complete artery occlusion, massive infarction with marked neurological deficit, intracranial hemorrhage, intracranial brain tumors, contraindicated to antithrombotic and/or anticoagulant, pregnant women, and patients susceptible to follow-up loss were excluded. Results This study involved 17 patients evaluated for ischemic events in the vertebrobasilar system, with a mean age of 58.47 ± 9.41 years. The most prevalent comorbidity was a previous transient ischemic attack (TIA) in 15 patients (88.2%), followed by hypertension in 12 patients (70.6%), diabetes and hyperlipidemia in 10 patients each (58.8% for both). Ischemic heart disease was present in 6 patients (35.3%), and smoking was reported by 5 patients (29.4%). The predominant stenosis location was intracranial in 11 patients (64.7%), with extracranial being the second most prevalent site in 6 patients (35.3%). The most prevalent kind of stenosis observed was atherosclerosis, affecting 11 patients (64.7%), followed by dissection in 6 patients (35.2%). The peri-procedural outcomes were good in 15 patients (88.2%) and bad in 2 patients (11.8%). The modified Rankin score (MRS) score was significantly decreased after 5-month follow-up than pre-operative. There was no statistically significant difference between extracranial and intracranial stenosis regarding the final outcome, residual stenosis, or peri-procedural complications. Conclusions Our findings emphasize the potential advantages of stenting for carefully chosen individuals with symptomatic vertebrobasilar stenosis and simple lesion morphologies (Mori types A and B). However, further research is needed for patient selection and therapy optimization.